Multiple intelligences theory and its appication in the sixth grade of basic english education - Alaña Quiñónez, Alexandra; Saquinaula, Juan Diego
This thesis emphasizes the importance of the process of teaching the English language to students from 9 to 10 years old. It helps teachers with some strategies, goals and techniques to improve the teaching of English. This process of teaching and learning will improve new knowledge for the integral formation of the students. So, this thesis proposes appropriate techniques in a clear and easy way to help students. It is also geared according to the age of the students. There is some need for the students and the teachers to be creative in order to reach their goals. The idea is to incorporate theory into practice and overcome inhibitions and boredom in the classroom by teaching English through an easy way. Teachers may use this textbook as a tool to improve their methodology in the teaching process and thus become better professionals.